Recognition and Prevention of Bed Separation Water: Based on Trapezoid Platform Model. (18th February 2021) - Hu, Ru; Wu, Jiwen; Zhai, Xiaorong; Liu, Wei
Abstract : In recent years, bed separation water inrush, as a new type of water disaster, has posed serious threat to mining safety in China's many coal mines. This study focused on periodic water inrush accidents in the No. 7335 working face owned by Xuzhuang Coal Mine, Jiangsu Province, China. Based on the theory of key strata, the formation positions of the separation layer in the overlying strata were first identified; next, the trapezoid platform model of the fracture of the overlying strata was introduced for illustrating the evolutional process of the bed separation space and accurately calculating the position and the geometrical morphology of the bed separation space. On that basis, the relation between the fracture of the overlying stratum and the inrush of bed separation water was revealed with the use of the plate theory. Moreover, the prevention and control measures of the bed separation water were formulated. Research show that the arrangement of the diversion drilling holes can successfully eliminate the threat of the bed separation water to the lower working face.